Association Between Reproductive Health Knowledge and Menarche Preparedness Among Elementary School Girls in Bogor Regency, Indonesia - Masluroh; Layyinatul Fuadah; Yuyun Sunarsih; Mega Aprilia; Lusiana Novita; Asih Handayani; Kusnanto (Journal of Innovative and Creativity, 2026)
Menarche marks an essential stage in female reproductive maturity. However, many young girls lack adequate knowledge and emotional preparedness, which may lead to anxiety, confusion, and negative attitudes toward menstruation. This study aimed to analyze the relationship between reproductive health knowledge and menarche preparedness among elementary school girls in Bogor Regency, Indonesia. A cross-sectional study was conducted among 72 fifth- and sixth-grade students at SDN Sukamaju 01 Jonggol, Bogor Regency. Total sampling was employed, and data were collected using a validated and reliable questionnaire (Cronbach’s α = 0.82). Descriptive statistics and Spearman’s rank correlation test were used to examine the association between knowledge and readiness, with a 95% confidence level. The mean age of participants was 11.2 ± 0.7 years. Most respondents demonstrated high reproductive health knowledge (59.7%), while 92% were categorized as unprepared for menarche. The Spearman correlation test revealed no significant association between knowledge and preparedness (rₛ = 0.011, p = 0.924). Although students’ knowledge of reproductive health was generally high, emotional and practical readiness for menarche remained low. These findings indicate that increasing knowledge alone is insufficient to ensure preparedness. Comprehensive, school-based reproductive health education programs that integrate cognitive, affective, and psychomotor aspects—along with parental involvement—are strongly recommended.